2022
DOI: 10.1155/2022/8468896
|View full text |Cite
|
Sign up to set email alerts
|

GABPB1-AS1 Promotes the Development of Osteosarcoma by Targeting SP1 and Activating the Wnt/β-Catenin Pathway

Abstract: In this study, the role of GABPB1-AS1 in osteosarcoma (OS) was analyzed. The expression of GABPB1-AS1 in different OS cell lines U2OS, HOS, MG63, and hFOB1.19 was detected. SiRNA GABPB1-AS1 was transfected with U2OS and HOS cell lines. The effects of GABPB1-AS1 silencing on proliferation, clonal formation, and migration of U2OS and HOS were detected by CCK-8 method, plate cloning method, and Transwell chamber. Western blot analysis was used to detect the protein levels of SP1, Wnt, β-catenin, c-Myc, and SOX2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For its role in cancer, GABPB1-AS1 was found to be upregulated in glioma tissues and associated with advanced WHO grades [22]. It was also found that silencing of GABPB1-AS1 could significantly inhibit the proliferation, clonal formation, migration, and epithelial-mesenchymal transformation of osteosarcoma by acting the SP1/Wnt/β-catenin signaling pathway [23]. However, there is still no study investigated the specific role of GABPB1-AS1 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…For its role in cancer, GABPB1-AS1 was found to be upregulated in glioma tissues and associated with advanced WHO grades [22]. It was also found that silencing of GABPB1-AS1 could significantly inhibit the proliferation, clonal formation, migration, and epithelial-mesenchymal transformation of osteosarcoma by acting the SP1/Wnt/β-catenin signaling pathway [23]. However, there is still no study investigated the specific role of GABPB1-AS1 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…GABPB1 associates with the alpha subunit to form a tetrameric configuration that actively enhances the transcription of a myriad of genes, including those involved in antioxidant defense mechanisms, such as Peroxiredoxin 5 (PRDX5), which is highly expressed in HCC tissues and associates with poor prognosis of patients [ 137 , 138 ]. The lncRNA GABPB1-AS1 is the antisense transcript of GABPB1 mRNA [ 139 ]. The expression of GABPB1-AS1 might fluctuate in response to stress stimuli [ 132 , 140 ].…”
Section: Ferroptosis-related Lncrnas In Hcc Progression and Prognosismentioning
confidence: 99%
“…Several reports showed the involvement of the Wnt/beta-catenin signaling pathway in OS tumor development and metastasis [81]. The SP1/Wnt/β-catenin signaling pathway plays a vital role in GABPB1-AS1-mediated OS tumorigenesis [82]. Melittin inhibits lung metastasis of human OS mediated by the Wnt/β-catenin signaling pathway [83].…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%